Assessment of a sequentially turbocharged diesel engine on real-life driving cycles. (16th April 2009) - Galindo, Jose; Climent, Hector; Guardiola, Carlos; Tiseira, Andres; , J. Portalier
The article presents the development of the control manager of a parallel sequential turbocharger system. This control manager must decide the transition between the different operation modes of the boosting system. The control manager must protect the system from surge and over-speed risks.The methodology followed in the development process was based on the use of concurrence survey data from a similar engine, the simulation with a 1D code and finally the assessment on engine test bench. Real-life driving cycles were used during the development process, which were acquired in three different driving scenarios (city, road and mountain road).